AutoCAD® 2018 and AutoCAD LT® 2018 essentials - Onstott, Scott (Sybex, a Wiley brand, 2017)
Provides a full-color, task-based approach to mastering this powerful software. Straightforward, easy-to-follow instruction pairs with real-world, hands-on exercises to help you quickly get up to speed with core features and functions; screenshots illustrate tutorial steps to help you follow along, and each chapter concludes with a more open-ended project so you can dive in and explore a specific topic in-depth.